Design of Nonuniform Filter Bank Transceivers for Frequency Selective Channels. (8th November 2006) - Chiang Chiang, Han-Ting Han-Ting; Phoong Phoong, See-May See-May; Lin Lin, Yuan-Pei Yuan-Pei
Abstract : In recent years, there has been considerable interest in the theory and design of filter bank transceivers due to their superior frequency response. In many applications, it is desired to have transceivers that can support multiple services with different incoming data rates and different quality-of-service requirements. To meet these requirements, we can either do resource allocation or design transceivers with a nonuniform bandwidth partition. In this paper, we propose a method for the design of nonuniform filter bank transceivers for frequency selective channels. Both frequency response and signal-to-interference ratio (SIR) can be incorporated in the transceiver design. Moreover, the technique can be extended to the case of nonuniform filter bank transceivers with rational sampling factors. Simulation results show that nonuniform filter bank transceivers with good filter responses as well as high SIR can be obtained by the proposed design method.